PRODUCT PLANNING AND CONTROL USING THE CRITICAL PATH METHOD - Julyanto, Octoberry; Wirani, Ayu Puspa; Agustina, Hartanti (IJOSMAS, 2021)
Every company, both private companies and individuals, certainly has the goal of getting the maximum possible profit from the business concerned and completing work according to a predetermined schedule. elements that are no less important than the success of a delivery of raw materials, and what is more important is to create a sense of satisfaction for the customer either quality, cost or time. The method used in this study is the CPM method. CPM is a network analysis that seeks to optimize the total project cost by reducing the total project completion time concerned. Microsoft Projects is designed to assist project managers in developing plans, assigning resources to tasks, tracking progress, managing budgets and analyzing workloads. The results of project calculations at the initial conditions with 65 working days normally without using overtime the company spent Rp. 108,623,550, - whereas after accelerating the fabrication time for 3 days from 65 days to 62 days the company spent more project costs of Rp. 127,691,810, -. Based on the results of the crashing this program, the company can anticipate project delays and for achieve a change in project completion time of 62 days and avoid a penalty penalty of 20% of the project value and the company can work on other project work.